2018
DOI: 10.1139/cjce-2017-0114
|View full text |Cite
|
Sign up to set email alerts
|

Strength behavior of plain cement concrete subjected to true triaxial compression

Abstract: True triaxial compression test was conducted on 100 mm × 100 mm × 100 mm cubical sample of plain cement concrete using the true triaxial testing machine. A total of 30 tests were conducted on two concrete mixes having characteristic strengths of 24.39 MPa and 34.67 MPa. The minor and intermediate principal stresses were varied from 2.5 MPa to 10 MPa and 2.5 MPa to 30 MPa respectively. The samples were loaded until failure under the stress rate of 1 MPa/min. The failure mode and direction of fracture planes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Saurav carried out a true triaxial test on cubical sample of plain cement concrete. The results show that the ratio of intermediate and minor principal stress had an incremental effect on the strength of the concrete [4]. Huai-shuai studied the triaxial compressive strength and deformation of air-entrained concrete under freeze-thaw cycles [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Saurav carried out a true triaxial test on cubical sample of plain cement concrete. The results show that the ratio of intermediate and minor principal stress had an incremental effect on the strength of the concrete [4]. Huai-shuai studied the triaxial compressive strength and deformation of air-entrained concrete under freeze-thaw cycles [5].…”
mentioning
confidence: 99%
“…An octahedral failure criterion was developed for asphalt mixture [19,20]. Qun compared the strength analysis theory with the traditional theory [21].Compared with the research in the geotechnical field [1][2][3][4][5][6][7][8][9][10][11][12][13][14], despite some research on some pavement materials strength under complex stresses being reported [15][16][17][18][19][20][21], it is necessary to study the true triaxial strength of the two most important pavement materials in China more deeply: asphalt mixture and cement-stabilized macadam with respect to, for example, the impact of intermediate principal stress on different gradations of the same type of mixtures. These studies will help to more accurately guide the pavement materials' composition design and even to provide a solution for early cracking of pavements.In this paper, a true triaxial test will be conducted on different gradations of asphalt mixture and cement-stabilized macadam, using a simple proprietary true triaxial apparatus, to examine the effect of intermediate principal stress on their strengths.…”
mentioning
confidence: 99%
“…Mogi found that in true triaxial testing of many rock samples, the effect of the intermediate principal stress must be considered for rock [21]. The results of complex stress tests for concrete indicate that the intermediate principal stress also has a marked effect on the strength of concrete [27,28]. We can conclude that the intermediate principal stress effect is an inherent mechanical behavior of many materials.…”
Section: Introductionmentioning
confidence: 84%
“…The mechanism for such deviations is mainly attributed to the differences in the physical properties of RA and the influence of the bending effect, rotation effect, and friction effect on the accuracy of trial data. Due to the combined factors By substituting Equation (12) into Equation (11), the relationship between the normal stress and shear stress of recycled concrete under the influence of the RA replacement rate was obtained, as shown in Figure 13 and Equation (13).…”
Section: Octahedral Stress Spacementioning
confidence: 99%
“…Therefore, research on the uniaxial mechanical properties alone has obvious shortcomings, which may lead to the problem of insufficient or excessive use of material. Rukhaiyar, S. and Zeng, S. et al [ 12 , 13 ] carried out a systematic study on the multiaxial mechanical properties of ordinary concrete and analyzed the influence of loading method and lateral stress on the multiaxial mechanical properties. On such a basis, a corresponding failure criterion and constitutive model were proposed.…”
Section: Introductionmentioning
confidence: 99%